ANALISIS POTENSI OBYEK WISATA MANGROVE SUNGAI KUPAH KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Parhusip, Nancy Boru; Buwono, Sri; Anasi, Putri Tipa (Universitas Tanjungpura, 2023)
This research is entitled Analysis of Potential Tourism Objects of the Kupah River Mangrove District, Sungai Kakap District, Kubu Raya Regency. Where Sungai Kupah Village is one of the villages in Kubu Raya Regency which has potential in the field of tourism so that Sungai Kupah Village was developed into a Sungai Kupah Mangrove Tourism Object. The Kupah River Mangrove Tourism Object has entered the top six of the Pesona Indonesia 2021 award and in 2022 it is included in the top 300 of the Indonesian Tourism Village Award. The purpose of this study was to determine the conditions and potential of the Kupah River Mangrove Tourism object. This study uses qualitative methods with descriptive analysis. Sources and data in this study were research objects in the Kupah River mangrove tourism object and the data were the results of field observations and from interviews with tourism managers, the Kubu Raya tourism office, and also visitors to the Kupah River mangrove tour. The results of this study indicate that the conditions in the Sungai Kupah Mangrove Tourism Object area from the 3A tourism approach are quite adequate, although there are still a number of things that need to be improved and monitored. In terms of the potential of this Mangrove Tourism object, the potential that is owned is quite a lot of interest, visitors can enjoy synsets and views of the estuary of the river, and also this tourist object can be used as a means of education.